Globalization and the Rise of the Entrepreneurial Economy - D. Audretsch; Mark Sanders (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2008)
This paper argues that recent trends in the global economy have led to a shift in developed countries' comparative advantage from mature industrial to early stage entrepreneurial production. We develop a three stage product life cycle model in which we distinguish between life cycle stages characterized by new, mature and off-shored production. In that model we analyze the impact of a level shock in the supply of unskilled labor in the South, a decrease in the level of political risk associated with outward foreign direct investment (off-shoring), and the widespread diffusion of a general purpose technology such as ICT. Due to endogenous responses in the allocation of entrepreneurial activity, the above shocks all result in a shift in the comparative advantage of developed countries towards new varieties, which corresponds to activities in the early stages of the product life cycle. Moreover, because entrepreneurs also serve as the agents that move varieties between life cycle stages, their value added increases due to globalization and technical change. By contrast, the factors of production employed in the mature stage of the life cycle, e.g. low skilled northern labor, become less valuable. Thus, the model predicts the emergence of an entrepreneurial economy in the North as the South opens up to trade and industrializes.
Keywords: 330; Product Cycles; International Trade; Entrepreneurship; Globalization